HASTY-dependent miRNA cell-to-cell movement is required for systemic pathogen resistance in Arabidopsis - Musso, Manuel (2026)
Plant defenses against pathogens are tightly regulated through complex gene expression control mecha- nisms. Precise activation and repression of defense-related genes are crucial for balancing the trade-off between growth and immunity. MicroRNAs (miRNAs) play a well-established role in the local regulation of plant–microbe interactions. While some miRNAs are also essential for systemic defense responses, their mechanisms of action, biogenesis, and long-distance mobility remain largely unexplored. Here, we show that HASTY (HST), a key factor in miRNA biogenesis and intercellular movement, is required for systemic defense activation. Impaired miRNA mobility in hst mutants correlates with the absence of systemic re- sponses. In infected tissues, HST may enhance the co-transcriptional processing of specific primary miR- NAs, thereby promoting cell-to-cell movement of their mature forms and contributing to systemic defense activation. Furthermore, two miRNAs that exhibit increased mobility during systemic defense induction are required for a proper systemic response. Notably, restoring miRNA mobility in the hst mutant without altering miRNA abundance, or complementing it with a version of HST expressed exclusively in companion cells, is sufficient to restore systemic defense induction, highlighting the critical role of miRNA cell-to-cell movement. Together, these findings elucidate the role of HST in plant immunity, linking miRNA biogenesis and mobility to the fine-tuned regulation of systemic defenses.